2013
DOI: 10.1016/j.supflu.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal conversion of glucose in multiscale batch processes. Analysis of the gas, liquid and solid residues

Abstract: Hydrothermal conversion is an interesting process to transform (very) humid biomass into high energy vectors or valuable products in the liquid or solid state. In the supercritical domain, water becomes a solvent for organics as well as a reactant, and thus the cellulosic content is effectively hydrolyzed into glucose, largely considered as its model molecule. The kinetics of glucose decomposition during the heating step in the batch reactor were investigated through the analysis of glucose concentration. Gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…For instance, Cantero, et al 49 reported a total conversion of glucose in 40 seconds at 300 C. Yu-Wu, et al 50 showed similarly that glucose undergoes fast degradation above 250 C. The complete conversion of glucose was also detected by Castello et al 51 aer a few seconds of residence time at 400 C. In the absence of NaOH, hydrothermal conversion of monosaccharides produces mostly water-soluble organic molecules, and an important amount of char (approximately 40 wt% of the initial mass). The addition of NaOH strongly inuences the conversion, notably by increasing the bio-oil yield and reducing the char yield.…”
Section: Hydrothermal Conversion Of Monosaccharides: Glucose and Xylosementioning
confidence: 99%
“…For instance, Cantero, et al 49 reported a total conversion of glucose in 40 seconds at 300 C. Yu-Wu, et al 50 showed similarly that glucose undergoes fast degradation above 250 C. The complete conversion of glucose was also detected by Castello et al 51 aer a few seconds of residence time at 400 C. In the absence of NaOH, hydrothermal conversion of monosaccharides produces mostly water-soluble organic molecules, and an important amount of char (approximately 40 wt% of the initial mass). The addition of NaOH strongly inuences the conversion, notably by increasing the bio-oil yield and reducing the char yield.…”
Section: Hydrothermal Conversion Of Monosaccharides: Glucose and Xylosementioning
confidence: 99%
“…Hydroquinone was found to have a high reactivity toward the formation of tars but not hydrochar . Yu-Wu et al analyzed the liquid and solid products in addition to gaseous products during HTG of glucose for potential applications . Specifically, HMF derived from liquid products and spherical nanoparticles could be upgraded into high-value added products, and the energetic gaseous products including H 2 , CH 4 , and C 2 H 6 could be concentrated as biofuels …”
Section: Hydrothermal Treatment Of Model Compounds To Chemicals Fuels...mentioning
confidence: 99%
“…237 Specifically, HMF derived from liquid products and spherical nanoparticles could be upgraded into high-value added products, 237 and the energetic gaseous products including H 2 , CH 4 , and C 2 H 6 could be concentrated as biofuels. 237…”
Section: Htl Of Saccharidesmentioning
confidence: 99%
“…Various reactor configurations have been employed for the SCWG of biomass. Batch, tubular, and continuous stirred tank reactors are majorly used in the biomass gasification using SCFs. Fluidized bed and diamond anvil cell reactors are two emerging configurations for biomass gasification in SCW.…”
Section: Biomass Gasification In Supercritical Watermentioning
confidence: 99%